Entwicklung eines Kosten und Nutzen umfassenden Modells zur Wahl des optimalen Behälters - Berbig, Dominik (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2014)
In order to guarantee efficient material supply of production areas, it is crucial to choose the adequate tote carrier for every single part number. Choosing a tote carrier is subject to many parameters. Yet, surveys show that this choice is often based only on the size, ignoring other aspects. This means wrong choices and wasted capital. Thus, an approach to solve this issue, a new model and possible benefits are presented.